Lessons Learnt From the Residential Zero Carbon District Demonstration Project, Governance Practice, Customer Response, and Zero-energy House Operation in Japan - Li, Yanxue; Zhang, Xiaoyi; Gao, Weijun; Qiao, Jiuli (Frontiers in Energy Research, 2022)
Building sector is undergoing a low-carbon transition feature applications of energy-efficient technologies and management innovations. Herein, we contribute to the study of the residential zero carbon district demonstration project in Japan, introducing smart practices and examining occupants’ awareness. We proposed a questionnaire survey covering more than 400 smart zero energy house owners that looks beyond the technologies for smart energy management and recognizes how the residential consumers engaged and perceive delivered energy saving and cost reduction issues, their usage frequency of home energy management system information-based services is also examined considering the impact of household income and occupants’ age variables. Overall, the respondents’ energy and cost-saving awareness vary widely, results argue the effectiveness of the visual-based service in engaging end-users in responsive energy system management. In the context of the detailed operational performances of real zero energy houses, we find evidence that automatic control has reshaped the characteristics of intraday energy balance and gives consumers greater control over their own energy bills. The findings clearly show the detailed role of integrated energy-efficient technologies over typical periods, grid-connected photovoltaic system plays a significant role in the realization of net annual zero electricity balance, micro-cogeneration’s contribution to zero energy house’s energy self-sufficiency largely depends on the building heating load.